2017
DOI: 10.5935/1518-0557.20170041
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effect of overweight in assisted reproduction treatment outcomes

Abstract: ObjectiveTo assess Body Mass Index (BMI) effects on the results obtained from ICSI cycles.MethodsWe studied 266 ICSI cycles performed between January 2014 and December 2016. The patients were grouped according to their BMI in: Normal (18.5-24.9), Overweight (25.0-29.9) and Obese (>30). We compared the following variables between the groups: number of antral follicles, ovarian stimulation length, gonadotropin dose used, maximum estradiol level, follicles developed/antral follicles, retrieved oocytes/developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…This phenomenon is most often found in women of advanced maternal age, mainly because of reduced ovarian reserve caused by accelerated follicular loss ( 18 ). In some cases, however, a low ovarian response might be seen in good ovarian reserve patients caused by a suboptimal gonadotropin dosage used for OS, for example in obese women ( 19 ), or due to the presence of genetic polymorphisms affecting endogenous gonadotrophins or their receptors ( 20 22 ). Both conditions ultimately alter the response of recruitable follicles to exogenous gonadotrophins ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is most often found in women of advanced maternal age, mainly because of reduced ovarian reserve caused by accelerated follicular loss ( 18 ). In some cases, however, a low ovarian response might be seen in good ovarian reserve patients caused by a suboptimal gonadotropin dosage used for OS, for example in obese women ( 19 ), or due to the presence of genetic polymorphisms affecting endogenous gonadotrophins or their receptors ( 20 22 ). Both conditions ultimately alter the response of recruitable follicles to exogenous gonadotrophins ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the final analysis, 105 eligible studies (19 prospective and 86 retrospective cohort studies) were included, involving more than 271,632 pregnant women (Figure 1). 14,15,28–130 The main characteristics of included studies were summarized in Table S1. In total, 100 studies reported the association between maternal BMI and CPR among pregnant women undergoing ART, among which 53 reported MR and 51 reported LBR (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Non-obese subjects (BMI < 25 kg/m 2 according to the BMI classification for Asian population) were recruited because we would like to avoid the confounding effects of obesity on IVF treatment as a previous publication revealed that obesity could have negative impacts on oocyte maturation, ovulation, endometrial development, and implantation. 33 The exclusion criteria were history of endocrine diseases (i.e. hypo/hyperthyroidism, Cushing’s syndrome, diabetes, and congenital adrenal hyperplasia), hormonal contraceptive use within two months (i.e.…”
Section: Methodsmentioning
confidence: 99%